Characterize the mechanical properties of selected type of coastal plastic waste - Mohd Hafiz, Ismail (2012)
Human are heavily dependent on the sea for economic and sources of high-protein food.In the past 10 years,coastal plastic pollution has extremely increased and this circumstance may affect human healthiness,difficulties to marine activities,and decreasing of quality of seawater.Not only plastic is made from a non-renewable resource,but it is generally a non-biodegradable material which made biodegradation process is very slow.Due to that recycling of coastal plastic waste is one of possible measures to be taken to tackle this issue.However,because of long exposure to the seawater and direct sunlight,the mechanical properties of coastal plastic waste would differ from the commercial plastic.The objectives of this study are to characterize mechanical properties of coastal plastic waste and compare the mechanical properties of coastal plastic waste with the commercial plastic and to analyse the differences of mechanical properties between coastal plastic waste and commercial plastic.Four types of common plastic; Polypropylene (PP),Polyethylene (PE),Polyethylene Terephthalate (PET),and Polyvinyl Chloride(PVC)are used as samples.These samples are collected,cleaned,and sorted according to type of plastics before being shredded.Then samples is melted and formed into a continuous profile via extruder and palletized into pallet-size samples.Next, samples are moulded into desired shape in accordance with American Society for Testing and Materials (ASTM) standard and tested utilizing Universal Testing Machine (UTM).From all results obtained,the mechanical properties for all type of coastal plastic wastes differ from mechanical properties of commercial plastic.This is due to the presence of salt in seawater and also direct sunlight towards the plastic waste which lead to degradation.It is recommended that other type of plastics should be used as samples and other mechanical properties should be studied in order to differentiate properties of coastal plastic waste and commercial plastic precisely.